Contrasting climate velocity impacts in warm and cool locations show that effects of marine warming are worse in already warmer temperate waters. Issue 1 (4th October 2021) - English, Philina A.; Ward, Eric J.; Rooper, Christopher N.; Forrest, Robyn E.; Rogers, Luke A.; Hunter, Karen L.; Edwards, Andrew M.; Connors, Brendan M.; Anderson, Sean C.
Abstract: Species responses to climate change are often measured at broad spatiotemporal scales, which can miss the fine‐scale changes that are most relevant to conservation and fisheries management. We develop a scaleable geostatistical approach to assess how juvenile and adult fish distributions have been shaped by changes in bottom temperature and dissolved oxygen over a recent decade of warming in the northeast Pacific. Across 38 demersal fishes, biomass trends were associated negatively with warming and positively with dissolved oxygen, but when trends in both biomass and climate were converted to velocities—the speed and direction a population would have to move to maintain consistent conditions—the effect of temperature change differed depending on local conditions. In the warmest locations, warming velocities were associated with negative biotic velocities for 19 of 69 species‐maturity combinations, and yet were almost always associated with stable or positive biotic velocities in the coolest locations (64 of 69). These spatially consistent biomass declines (negative biotic velocities) in the warmest locations and increases in cooler locations suggest a redistribution of species with the potential for new ecological and fisheries interactions. After controlling for temperature, the more spatially consistent effects of dissolved oxygen were often negative, suggesting a mechanism other than hypoxia avoidance—potentially changes in primary production. Our approach identifies the species and locations that are most sensitive to observed changes in the environment at any scale, thus facilitating future vulnerability assessments.